Microscopic evaluation of vesicles shed by erythrocytes at elevated temperatures. Issue 11 (20th August 2013) - Moore, Timothy; Sorokulova, Iryna; Pustovyy, Oleg; Globa, Ludmila; Pascoe, David; Rudisill, Mary; Vodyanoy, Vitaly
ABSTRACT The images of human erythrocytes and vesicles were analyzed by a light microscopy system with spatial resolution of better than 90 nm. The samples were observed in an aqueous environment and required no freezing, dehydration, staining, shadowing, marking, or any other manipulation. Temperature elevation resulted in significant concentration increase of structurally transformed erythrocytes (echinocytes) and vesicles in the blood. The process of vesicle separation from spiculated erythrocytes was video recorded in real time. At a temperature of 37°C, mean vesicle concentrations and diameters were found to be 1.50 ± 0.35 × 106 vesicles per microliter and 0.365 ± 0.065 μm, respectively. The vesicle concentration increased approximately threefold as the temperature increased from 37 to 40°C. It was estimated that 80% of all vesicles found in the blood are smaller than 0.4 μm. Accurate account of vesicle numbers and dimensions suggest that 86% of the lost erythrocyte material is lost not by vesiculation but by another, as yet, unknown mechanism. Microsc. Res. Tech. 76:1163–1170, 2013. © 2013 Wiley Periodicals, Inc.